Rf receiver system for cognitive radio application - Xue, Yuan Zhong. (2010)
In order to design RF receiver system, different topologies has been researched in the current industry. A novel RF receiver system with ability of spectrum sensing and demodulation had been successfully designed to meet the requirement for the project. It was designed using MATLAB and simulated based on Simulink. The RF receiver, recover the carrier signal as desired, was able to detect the frequency of input signal and demodulate the received signal. Recommendations for future work include looking into the spectrum sensing method for a more simply scheme and adding a feedback voltage to control VCO for killing the phase error etc.